Facial Nerve Schwannoma of the Cerebellopontine Angle: A Diagnostic Challenge - Lassaletta, Luis (2002)
Facial nerve schwannomas are rare lesions that may involve any segment of the facial nerve. Because of their rarity and the lack of a consistent clinical and radiological pattern, facial nerve schwannomas located at the cerebellopontine angle (CPA) and internal auditory canal (IAC) represent a diagnostic and therapeutic challenge for clinicians. In this report, a case of a CPA/IAC facial nerve schwannoma is presented. Contemporary diagnosis and management of this rare lesion are analyzed.